Intuitive and Counterintuitive Mechanisms for Dosing, Controlling, and Renegotiating Leverage (2023-2025) (National Administration Journal, 2025)
The objective of this study is to determine the effectiveness of applying a package of adapted counterintuitive measures (PAQ-MC) to sustainably reduce over-indebtedness among economic agents in Costa Rica during the 2023–2025 period. The research adopts a quantitative approach and a longitudinal experimental design, with control and experimental groups of 51 participants each.The intervention aims to prevent consumers from exceeding the critical debt threshold (50%–60%) through a combination of methods. To statistically validate the results, the paired-sample Student’s t-test was used to compare debt levels before and after the intervention. This tool adds rigor and strengthens the validity of the findings.Results show a p-value of 0.0012, below the 5% significance level, allowing rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (H₁) with a 95% confidence level. The mean increased from 2.725 to 3.118, with a difference of +0.392, attributed to the treatment. It is concluded that this difference is not due to chance, but to the PAQ-MC intervention.This study represents an innovative proposal, with no documented precedents in Costa Rica evaluating the experimental impact of counterintuitive measures on consumer financial behavior. In a context of growing indebtedness, this research is expected to serve as a guiding light for those facing the darkness of debt. Due to budget constraints, two balanced random groups were used.
Keywords: Over-Indebtedness; liabilities; insolvency; illiquidity; intuitive; counterintuitive